P115 Cigarettes smoke extract induces inflammatory gene expression in human bronchial epithelial cells. (15th November 2017) - Alshehri, M; Brand, O; Alqarni, A; Pasini, A; Pang, L
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is an inflammatory disorder of the respiratory tract characterised by airflow obstruction. It is increasingly recognised that the innate immune pattern-recognition receptors may contribute to airway inflammation in COPD in response to environmental factors such as cigarette smoke (CS). One pattern-recognition receptor that has recently come to attention in chronic airway disease is the cell surface receptor for advanced glycation end products (RAGE). RAGE also exists as a soluble form (sRAGE) that primarily functions as receptor decoy and an endogenous inhibitor of RAGE signalling. Clinical studies show that smokers with or without COPD have significantly greater levels of RAGE expression in airway epithelial cells compared with never smokers. However, the role of RAGE in mediating CS-induced inflammatory gene expression has not been understood. We hypothesise that CS can induce RAGE expression, sRAGE reduction, and inflammatory gene expression in human bronchial epithelial cells (BEAS-2B). Method: Confluent BEAS-2B cells were treated with different concentrations of Cigarette Smoke Extract (CSE) (1%, 2.5%, and 5%) for 24 hours. Western blotting was used to assess protein expression of RAGE in cell lysate. ELISA was used to measure interleukin 6 (IL-6), CXCL1 (GRO-α), CXCL5 (ENA-78), CXCL8 (IL-8), CXCL10 (IP-10), CCL11 (eotaxin), and sRAGE in culture medium. Result: We found that IL-6 and CXCL8 releases were markedly increased by CSE in a concentration-dependant manner, but CXCL-1, CXCL5, CXCL10 and CCL11 could not be detected in both untreated and CSE-treated cells. Interestingly, RAGE was highly expressed in untreated cells and CSE treatment did not further increase its expression. Furthermore, sRAGE was also undetectable in both untreated and CSE-treated cells. Conclusion: These findings suggest that CSE can induce inflammatory gene expression in BEAS-2B cells. Further experiments are being conducted to explore the effect of CSE on other inflammatory gene expression and to investigate the role of RAGE in mediating CSE-mediated inflammatory response in BEAS-2B cells.